Ответы и объяснения

  • AlbuRin
  • светило науки
2013-07-25T08:30:57+00:00
{3х - 2(3у - 1) = -2      {3x - 6y + 2 + 2 = 0        {3x -6y + 4 = 0           {3x - 6y + 4 = 0
{2(х + 1) - 1 = 3у - 1   {2x + 2 - 1 -3y + 1 = 0    {2x - 3y + 2 = 0  |*(-2)  {-4x + 6y -4 = 0
Cложим  почленно  1-е  и  2-е  уравнение.
3х + (-4х) + (-6у) + 6у + 4 -4 = 0
-х = 0
х = 0
Полученное  значение  х = 0  подставим во  второе  уравнение.
2*0 - 3у - 2 = 0
-3у = 2                                                                                                                  у = 2/(-3)
у = -2/3
Ответ.  (0;    -2/3)
2013-07-25T09:16:24+00:00
3x-2(3y-1)=-2
2(x+1)-1=3y-1 
3х-6у+4=0
2х+2-1-3у+1=0
3х-6у+4=0
2х-3у+2=0/*(-2)
3х-6у+4=0
-4х+9у-4=0
-х=0
х=0
-6у+4=0
у=-2/3